Balanced Scorecard-Based Quality Management Strategy in Improving the Quality of Educational Services in Accredited Early Childhood Education Institutions - Saona, Saona (Generasi, 2025)
Backround: Quality management in Grade A accredited PAUD institutions requires comprehensive strategic frameworks that balance multiple performance dimensions while maintaining educational excellence. The Balanced Scorecard (BSC) offers a systematic approach integrating financial, customer, internal process, and learning and growth perspectives to enhance service quality and organizational effectiveness.Objective: This research aims to analyze BSC-based quality management strategy implementation in Grade A accredited PAUD institutions and evaluate their effectiveness in enhancing educational service quality across multiple performance dimensions.Method: Employing qualitative descriptive-analytical approach, this study examined six Grade A accredited PAUD institutions in Jakarta, Bandung, and Surabaya through semi-structured interviews with 25-30 key informants, observations of educational and administrative processes, focus group discussions with teachers and parents, and document analysis of strategic plans and performance records. Data were analyzed using thematic analysis procedures.Findings and Implications: Comprehensive BSC implementation correlates with superior service quality outcomes including higher parent satisfaction (4.54 vs 4.25), improved teacher retention (91% vs 81%), enhanced operational efficiency (88.7% vs 81.3%), and greater innovation capacity. Strategic integration across BSC perspectives, systematic performance monitoring, and balanced investment in organizational capabilities emerge as critical success factors.Conclusion: Findings inform institutional strategic management practices and policy development supporting PAUD quality enhancement. BSC-based quality management strategies effectively enhance PAUD service quality when implemented comprehensively with strategic integration, leadership commitment, stakeholder engagement, and sustained organizational development.